A Blended Active Learning Pilot: A Way to Deliver Interprofessional Pain Management Education - Victoria Wood; Lynda Eccott; Lesley Bainbridge (MDPI AG, 2013)
This article presents an innovative approach to interprofessional education that places learning in the context of a specific clinical area that is relevant to pharmacy students as well as students from a number of other health professions; in this case pain management. Interprofessional pain education that teaches a team approach to pharmacy students is essential for improving pain management practices. The interprofessional education model presented, based on a pilot of a series of interprofessional pain management modules, is designed to be flexible, using a modular format that incorporates both online and face-to-face learning. The model was developed as a means of overcoming some of the challenges, such as scheduling, which make the integration of interprofessional education into curricula difficult. This technology enabled education model has been piloted and implemented with groups of pharmacy students who were placed into teams with students from other disciplines such as medicine, nursing, and social work. This article presents the educational strategy and its development; describes the interprofessional pain management modules; discusses findings from three pilot evaluations of the modules; shares lessons learned; and highlights the strengths of the approach.